2014
DOI: 10.1002/chem.201402633
|View full text |Cite
|
Sign up to set email alerts
|

Vicinal Solvent Effect on Supramolecular Gelation: Alcohol Controlled Topochemical Reaction and the Toruloid Nanostructure

Abstract: Although solvent is the major component of the gel, it still remains unclear how the solvent molecules take part in the formation of the gel nanostructures in many gels. In this study it was observed that the vicinal effect on gel formation as well as their nanostructures, that is, the vicinal solvent molecules to the gelator, determine the molecular packing and their subsequent structures and properties. A naphthylacryl-conjugated L-glutamide gelator was found to form organogels in various solvents and nanofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…These results indicated that the halogen bond between pyridine group in Azopy‐C 10 and TFDIB was of great importance for gelation. Notably, the critical gelation concentration of Azopy‐C 10 •TFDIB in acetonitrile (2 wt%) was lower than that in ethanol (4 wt%) . This result would be attributed to the replacement of halogen bond by hydrogen bond between ethanol and pyridine group.…”
Section: Methodsmentioning
confidence: 89%
“…These results indicated that the halogen bond between pyridine group in Azopy‐C 10 and TFDIB was of great importance for gelation. Notably, the critical gelation concentration of Azopy‐C 10 •TFDIB in acetonitrile (2 wt%) was lower than that in ethanol (4 wt%) . This result would be attributed to the replacement of halogen bond by hydrogen bond between ethanol and pyridine group.…”
Section: Methodsmentioning
confidence: 89%
“…Wang et al . reported that a naphthylacryl‐conjugated L‐glutamide ( 4 ) forms organogel in non‐alcoholic solvents as well as alcoholic solvents . However, it was found that the gels obtained from alcoholic solvents undergo topochemical [2+2] reaction upon photoirradiation (Figure a), while the gels obtained from non‐alcoholic solvents were found to be photostable.…”
Section: [4+4] and [2+2] Reactions In Organic Gelsmentioning
confidence: 79%
“…Generally, the gel structures were deduced in many cases from the solid state structures of the gelators or powder patterns of the xerogels. It was proven by us, and others, no such one‐to‐one correlation exists between gel‐xerogel or gel‐solid state in terms of their supramolecular structures. In a way, the geometry of the product formed is anticipated to give way to deduce the geometry of supramolecular assemblies in gel or xerogels.…”
Section: Gel State Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The supramolecular gels have potential applications including sensing of biomolecules and ions, light-harvesting systems, [15][16][17][18][19] catalysis, 20 optoelectronic devices, 21 and as media for cell culture, tissue engineering and targeted drug delivery. [22][23][24][25][26][27][28][29] Many organic motifs such as steroids, 30 peptides, [31][32][33][34] ureas and amides, [35][36][37][38][39][40] sugars, 41 dendrimers, 42,43 and p-conjugated molecules 44,45 have been designed and developed as gelatos. But, most of these organic gelator molecules need to be synthesized by tedious procedures.…”
Section: Introductionmentioning
confidence: 99%